Education Promoted Secularization - Sascha O. Becker; Markus Nagler; Ludger Woessmann (Institute for the Study of Labor (IZA), 2014)
Why did substantial parts of Europe abandon the institutionalized churches around 1900? Empirical studies using modern data mostly contradict the traditional view that education was a leading source of the seismic social phenomenon of secularization. We construct a unique panel dataset of advanced-school enrollment and Protestant church attendance in German cities between 1890 and 1930. Our cross-sectional estimates replicate a positive association. By contrast, in panel models where fixed effects account for time-invariant unobserved heterogeneity, education – but not income or urbanization – is negatively related to church attendance. In panel models with lagged explanatory variables, educational expansion precedes reduced church attendance.
Keywords: Z12; N33; I20; 330; secularization; education; history; Germany